An imaging evaluation of the simultaneously integrated boost breast radiotherapy technique. Issue 3 (21st August 2015) - Turley, Jessica; Claridge Mackonis, Elizabeth
Abstract Introduction To evaluate in‐field megavoltage (MV) imaging of simultaneously integrated boost (SIB) breast fields to determine its feasibility in treatment verification for the SIB breast radiotherapy technique, and to assess whether the current‐imaging protocol and treatment margins are sufficient. Methods For nine patients undergoing SIB breast radiotherapy, in‐field MV images of the SIB fields were acquired on days that regular treatment verification imaging was performed. The in‐field images were matched offline according to the scar wire on digitally reconstructed radiographs. The offline image correction results were then applied to a margin recipe formula to calculate safe margins that account for random and systematic uncertainties in the position of the boost volume when an offline correction protocol has been applied. Results After offline assessment of the acquired images, 96% were within the tolerance set in the current department‐imaging protocol. Retrospectively performing the maximum position deviations on the Eclipse™ treatment planning system demonstrated that the clinical target volume (CTV) boost received a minimum dose difference of 0.4% and a maximum dose difference of 1.4% less than planned. Furthermore, applying our results to the Van Herk margin formula to ensure that 90% of patients receive 95% of the prescribed dose, the calculated CTV margins were comparable to the current departmental procedure used. Conclusion Based on the in‐field boost images acquired and the feasible application of these results to the margin formula the current CTV‐planning target volume margins used are appropriate for the accurate treatment of the SIB boost volume without additional imaging.